Hide-and-Seek: A Game Played between Parasitic Protists and Their Hosts - Kolářová, Iva; Valigurová, Andrea (Microorganisms, 2021)
After invading the host organism, a battle occurs between the parasitic protists and the host's immune system, the result of which determines not only whether and how well the host survives and recovers, but also the fate of the parasite itself. The exact weaponry of this battle depends, among others, on the parasite localisation. While some parasitic protists do not invade the host cell at all (extracellular parasites), others have developed successful intracellular lifestyles (intracellular parasites) or attack only the surface of the host cell (epicellular parasites). Epicellular and intracellular protist parasites have developed various mechanisms to hijack host cell functions to escape cellular defences and immune responses, and, finally, to gain access to host nutrients. They use various evasion tactics to secure the tight contact with the host cell and the direct nutrient supply. This review focuses on the adaptations and evasion strategies of parasitic protists on the example of two very successful parasites of medical significance, Cryptosporidium and Leishmania, while discussing different localisation (epicellular vs. intracellular) with respect to the host cell.
Keywords: host defence; parasitophorous sac; parasitic protist; intracellular; parasitophorous vacuole; epicellular; unicellular parasite; evasion strategies; Cryptosporidium; adaptation to parasitism; extracellular; Leishmania